Prealbumin as a Predictor of Prognosis in Patients With Coronavirus Disease 2019 - Luo, Ying; Xue, Ying; Mao, Liyan; Yuan, Xu; Lin, Qun; Tang, Guoxing; Song, Huijuan; Wang, Feng; Sun, Ziyong (Frontiers in Medicine, 2020)
Background The predictive value of prealbumin for the prognosis of coronavirus disease 2019 (COVID-19) was rarely investigated. Methods A total of 1,115 patients with laboratory-confirmed COVID-19 were enrolled at Tongji hospital from February to April 2020, and classified into fatal (n=129) and recovered (n=986) group according to the patient’s outcome. Prealbumin and other routine laboratory indicators were measured simultaneously. Results The level of prealbumin on admission was significantly lower in fatal patients than in recovered patients. For predicting the prognosis of COVID-19, the performance of prealbumin was better than most routine laboratory indicators, such as albumin, lymphocyte count, neutrophil count, hypersensitive C-reactive protein, d-dimer, lactate dehydrogenase, creatinine and hypersensitive cardiac troponin I. When the threshold of 126 mg/L was used, the sensitivity and specificity of prealbumin were respectively 78.29% and 90.06% in discriminating between fatal and recovered patients. Furthermore, a model based on the combination of nine indexes showed an improved performance in predicting the death of patients with COVID-19. Using the cut-off value of 0.19, the prediction model was able to distinguish between fatal and recovered individuals with a sensitivity of 86.82% and a specificity of 90.37%. Conclusions A lower level of prealbumin on admission may indicate a worse outcome of COVID-19. Immune and nutritional status may be vital factors for predicting disease progression in the early stage of COVID-19.